BEHAVIOUR OF OIL PALM BROOM FIBRE REINFORCED CONCRETE (Journal of Engineering Studies and Research, 2025)
Fiber reinforced concrete was developed by incorporating discrete fibers into the concrete mass to combat the brittle reaction of concrete. The durability of natural fibers such as oil palm broom was established through an experimental investigation in which the fiber was treated to an alkalization-related treatment procedure. The research is based on the investigation of the use of Oil Palm Broom Fibres (OPBF) in structural concrete to enhance the mechanical characteristics of concrete. The OPBF were subjected to an alkali treatment with the use of sodium hydroxide of 4 %, 6 %, 8 % and 10% with removal times of 1 hr, 2 hrs, 8 hrs and 24 hrs respectively. The flexural strength of OPBF concrete was determined after 28 days where the treated fibres were included in fresh concrete mix. The discrete OPBF of 75 mm length were washed and dried in open air and randomly included in the concrete at 0.3 % of the volume of the beam size 100 x 100 x 600 mm with mix ratio of 1:2:4 and water-cement ratio of 0.55 to assess the suitability and durability of the fibre in concrete. It was observed that the rate of water absorption of the treated fibres increase compared to untreated fibres and the treated OPBF with lkalization improves the flexural strength of concrete beam at a concentration of 6 % NaOH for a duration of 1hr and the SEM images of OPBF cross section shows dispersed cavities. The OPBF is appropriate for use in concrete as a brief discrete fibre reinforcement for low cost construction.
Keywords: alkalization, concrete, durability, flexural strength, oil palm broom fibre